Automata diagram for groups - Gan, Yee Siang; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (2013)
Automata act as the recognition devices to determine the types of languages a string belongs to, by using the transition graph. In the previous researches, the classical models of automata have been used to recognize the strings in languages. Recently, the relation of automata and Cayley table of the group have been studied to relate automata theory with group. In the study of automata and group theory, it has been found that automata diagram can be used to analyse properties of some groups such as Abelian groups and Permutation groups. Such automata that are used are modified finite automata and Watson-Crick finite automata. Thus in this paper, the definition and some properties of group in terms of automata diagram are given.